Local agenda 21 : action plan for sustainable development : case study for Shah Alam - Ahmad Azam, Nur Nabila; Mohamed Osman, Mariana (2012)
Sustainable development, which has been defined as a means to meet the needs of the present without compromising on the ability of future generations to meet their needs, is not a new term these days. One of the initiatives that have been taken by the government of Malaysia in realizing the idea of sustainable development is through the implementation of Local Agenda 21 (LA21). LA21 is a global action plan or blueprint for sustainable development at local level, which was adopted at the Earth Summit in Rio de Janeiro in 1992. LA21 is a reflection of a common consensus and political commitment of countries globally on sustaining development and environment cooperation. As such, this paper explains the role of LA21 as one of the efforts by the Malaysian government in achieving sustainable development. The objective of this paper is to describe the implementation of LA21 programs and activities carried out and planned by the local authority, community and private sector towards achieving sustainable development. A descriptive analysis was used to describe the Shah Alam’s LA21 projects in promoting sustainable development. The outcomes illustrated the significance of LA21 projects in facilitating Malaysia to achieve sustainable development.